2012
DOI: 10.1098/rspb.2012.1562
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex class II compatibility, but not class I, predicts mate choice in a bird with highly developed olfaction

Abstract: Mate choice for major histocompatibility complex (MHC) compatibility has been found in several taxa, although rarely in birds. MHC is a crucial component in adaptive immunity and by choosing an MHCdissimilar partner, heterozygosity and potentially broad pathogen resistance is maximized in the offspring. The MHC genotype influences odour cues and preferences in mammals and fish and hence olfactorybased mate choice can occur. We tested whether blue petrels, Halobaena caerulea, choose partners based on MHC compat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
130
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(136 citation statements)
references
References 62 publications
5
130
1
Order By: Relevance
“…46 Another recent study conducted on monogamous birds with highly developed olfaction shows that it is MHC class II molecules and not class I, which determine mate recognition. 47 In humans it has been demonstrated that different HLA types show preference or dislike for specific scents, suggesting that some volatile molecules responsible for these odors are mimicking some HLA-specific scent. 48,49 MHC class II molecules are responsible for immune response to external stimuli and it is thus a more suitable candidate than class I MHC for a possible olfactory function.…”
Section: Discussionmentioning
confidence: 99%
“…46 Another recent study conducted on monogamous birds with highly developed olfaction shows that it is MHC class II molecules and not class I, which determine mate recognition. 47 In humans it has been demonstrated that different HLA types show preference or dislike for specific scents, suggesting that some volatile molecules responsible for these odors are mimicking some HLA-specific scent. 48,49 MHC class II molecules are responsible for immune response to external stimuli and it is thus a more suitable candidate than class I MHC for a possible olfactory function.…”
Section: Discussionmentioning
confidence: 99%
“…In some passerine species, for example, structural plumage coloration, ultraviolet signals, and song performance correlate with male age and possibly influence female mate preferences (Siefferman and Hill 2005;Budden and Dickinson 2009;Kipper and Kiefer 2010), and foot color of blue-footed boobies is a dynamic sexually selected ornament that loses intensity with age (Torres and Velando 2003. Olfactory cues could also be used; mice and humans can use smell to discriminate between differently aged conspecifics (Mitro et al 2012), and some birds discriminate among conspecifics on the basis of their odor (Bonadonna and Nevitt 2004;Strandh et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…; range: 1 -4). Two individuals included in this study were only genotyped, using the method described in Strandh et al [9]. The correspondence between the two methods was tested by genotyping 36 individuals of the population using the two methods.…”
Section: (B) Y-maze Experimentsmentioning
confidence: 99%
“…The blue petrel (Halobaena caerulea) is a monogamous seabird with a particularly good sense of smell [18][19][20] that has been shown to preferentially mate with partners dissimilar at the MHC class II loci [9]. In this monomorphic species, males and females share parental duties equally [21,22], and mate choice is therefore thought to be reciprocal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation